2017
DOI: 10.5603/gp.a2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

The duration of pregnancy in ecologically-challenged area. The effects of environmental pollution with aromatic hydrocarbons on the angiogenesis and elements of the mesenchymal tissue of the human placenta

Abstract: Introduction:The literature presents only few reports regarding the effects of elevated levels of aromatic hydrocarbons (AH) on the functions of the human placenta. The effects of environmental contamination with AH (including phenol and 1-hydroxypyrene) have certain negative effects on parenchymal organs such as human placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Wierzba, on the other hand, has shown that, the foetus is protected by activation of adaptation and compensation mechanisms that are manifested as active angiogenesis and formation of new blood vessels that provide proper nutrition and oxygen supply to the foetus and significantly greater development of mesenchymal cells compared to the control group [28].…”
Section: Discussionmentioning
confidence: 99%
“…Wierzba, on the other hand, has shown that, the foetus is protected by activation of adaptation and compensation mechanisms that are manifested as active angiogenesis and formation of new blood vessels that provide proper nutrition and oxygen supply to the foetus and significantly greater development of mesenchymal cells compared to the control group [28].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the foetus is protected by activation of adaptation and compensation mechanisms that are manifested as active angiogenesis and formation of new blood vessels that provide proper nutrition and oxygen supply to the foetus and significantly greater development of mesenchymal cells compared to the control group [29].…”
Section: Resultsmentioning
confidence: 99%